Africa, rise to challenge : towards a Conference on Security, Stability, Development and Cooperation in Africa (CSSDCA) - Obasanjo, Olusegun; Mosha, Felix G. N.; Africa Leadership Forum (Abeokuta, Ogun State, Nigeria ; New York, N.Y., U.S.A. : Africa Leadership Forum, 1993)
A compilation of the papers from the Conference on Security, Stability, Development and Cooperation in Africa in 1992 at Kampala, Uganda.
Includes bibliographical references.
oif 02/04/15, ijb 06/02/2019
Loan
Keywords: Africa; African cooperation; National security; Africa; Africa